2005
DOI: 10.1038/nature03670
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of cotranslational translocation of vascular cell adhesion molecule 1

Abstract: Increased expression of vascular cell adhesion molecule 1 (VCAM1) is associated with a variety of chronic inflammatory conditions, making its expression and function a target for therapeutic intervention. We have recently identified CAM741, a derivative of a fungus-derived cyclopeptolide that acts as a selective inhibitor of VCAM1 synthesis in endothelial cells. Here we show that the compound represses the biosynthesis of VCAM1 in cells by blocking the process of cotranslational translocation, which is depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
148
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 15 publications
7
148
0
Order By: Relevance
“…Reagents for in vitro transcription, translation, and translocation assays were prepared and used as described previously (Fons et al, 2003, and references therein). Hun-7293 was obtained from D. Boger (The Scripps Research Institute), and it was tested in translocation assays of vascular cell adhesion molecule (VCAM)1 (our unpublished data) to have the same properties as those previously published for Cotransin and CAM741 (Besemer et al, 2005;Garrison et al, 2005). The p58 IPK sequence was analyzed using SignalP 3.0 (Bendtsen et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Reagents for in vitro transcription, translation, and translocation assays were prepared and used as described previously (Fons et al, 2003, and references therein). Hun-7293 was obtained from D. Boger (The Scripps Research Institute), and it was tested in translocation assays of vascular cell adhesion molecule (VCAM)1 (our unpublished data) to have the same properties as those previously published for Cotransin and CAM741 (Besemer et al, 2005;Garrison et al, 2005). The p58 IPK sequence was analyzed using SignalP 3.0 (Bendtsen et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The compound does not inhibit targeting of the VCAM1 nascent chains to the translocon, but although a salt-resistant tight complex is formed, translocation to the luminal side of the ER is prevented (35). Concurrently, Garrison et al (36) reported that the synthetic compound "cotransin," which has a structure very similar to CAM741, inhibits VCAM1 translocation and demonstrated that the inhibition involves the Sec61 channel but not accessory factors, such as TRAM, TRAP, and the Sec62/63 complex.…”
Section: N-terminal Cleavable Signal Peptides (Sp)mentioning
confidence: 99%
“…The SEAP fusions of the mouse VCAM1 SP plus additional four amino acid residues of the mature region, all VCAM1 SP mutants and constructs encoding fusions of the N-terminal tag to the SP were generated by PCR and subcloned into pcDNA3.1. The truncated VCAM1 cDNA, encoding the 112 amino acid residues subcloned into pcDNA3.1, has been described (35). The truncated VCAM1 cDNA encoding 182 amino acid residues was generated by PCR and subcloned into pcDNA3.1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations